The Adoption of E-Learning in Teaching and Learning Processes; an Option for Life-Long Education - Baginda Simaibang (Bandar Lampung University (UBL), 2013)
The objective of this study is to investigate the benefits of the adoption of electronic learning (E-Learning)in teaching and learning processes. E-Learning is an educational approach that utilizes computer technology, particularly digital technologies that are internet-based, to provide instruction and learning experiences. The definition of e-learning refers to a wide range of applications and processes designed to deliver instruction through electronic means. This means is normally employed over the network. It includes video streamings, video-conferencing through satellite transmission, online learning, web-based training (WBT), computer-based training(CBT), internet, intranet, PCs at work, school or home, interactive multimedia, games, simulations, flash animation, online tutorials, video and audio resources such as tapes, CD, and DVD. Research indicates that e-learning signals the paradigm shift in education and training that is in progress. It provides a new set of tools and instructional practices that overcome distance barriers, logistic costs and adds value to existing traditional learning process, such as classroom lectures, textbooks, video and CD-ROM. As computer technology is introduced, it immediately becomes integrated with the instructional technology that preceded it. This is called